PINK1 Is Selectively Stabilized on Impaired Mitochondria to Activate Parkin - Narendra, Derek P. (Public Library of Science, 2010)
Loss-of-function mutations in PINK1 and Parkin cause parkinsonism in humans and mitochondrial dysfunction in model organisms. Parkin is selectively recruited from the cytosol to damaged mitochondria to trigger their autophagy. How Parkin recognizes damaged mitochondria, however, is unknown. Here, we show that expression of PINK1 on individual mitochondria is regulated by voltage-dependent proteolysis to maintain low levels of PINK1 on healthy, polarized mitochondria, while facilitating the rapid accumulation of PINK1 on mitochondria that sustain damage. PINK1 accumulation on mitochondria is both necessary and sufficient for Parkin recruitment to mitochondria, and disease-causing mutations in PINK1 and Parkin disrupt Parkin recruitment and Parkin-induced mitophagy at distinct steps. These findings provide a biochemical explanation for the genetic epistasis between PINK1 and Parkin in Drosophila melanogaster. In addition, they support a novel model for the negative selection of damaged mitochondria, in which PINK1 signals mitochondrial dysfunction to Parkin, and Parkin promotes their elimination.